Multielectron effects in strong-field dissociative ionization of molecules - Gong, X.; Kunitski, M.; Betsch, K. J.; Song, Q.; Schmidt, L. Ph. H.; Jahnke, T.; Kling, Nora G.; Herrwerth, O.; Bergues, B.; Senftleben, A.; Ullrich, J.; Moshammer, R.; et al. (My University, 2014)
We study triple-ionization-induced, spatially asymmetric dissociation of N2 using angular streaking in an elliptically polarized laser pulse in conjunction with few-cycle pump-probe experiments. The kinetic-energy-release dependent directional asymmetry in the ion sum-momentum distribution reflects the internuclear distance dependence of the fragmentation mechanism. Our results show that for 5–35-fs near-infrared laser pulses with intensities reaching 1015 W/cm2, charge exchange between nuclei plays a minor role in the triple ionization of N2. We demonstrate that angular streaking provides a powerful tool for probing multielectron effects in strong-field dissociative ionization of small molecules.